2015
DOI: 10.2217/cer.15.33
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of daclatasvir/asunaprevir versus IFN-based regimens in genotype 1b hepatitis C virus infection

Abstract: DCV + ASV demonstrated superior efficacy and safety compared with A/R-based regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…DCV plus ASV was well tolerated in both studies with few AEs leading to treatment discontinuation. Consistent with phase 3 results, a network meta‐analysis found that this combination was more effective and better tolerated than pegIFN/RBV alone or combined with telaprevir, boceprevir or simeprevir .…”
mentioning
confidence: 56%
“…DCV plus ASV was well tolerated in both studies with few AEs leading to treatment discontinuation. Consistent with phase 3 results, a network meta‐analysis found that this combination was more effective and better tolerated than pegIFN/RBV alone or combined with telaprevir, boceprevir or simeprevir .…”
mentioning
confidence: 56%
“…Because no "head-to-head" studies comparing DCV/ASV versus PR and PIs/PR is available, data from a network meta-analysis (NMA) was used [ 19 ]. The main objective of this study was to compare the results of efficacy and tolerability of DCV/ASV, PR, PIs/PR among other alternatives, in different groups of patients.…”
Section: Methodsmentioning
confidence: 99%
“…The review of published literature revealed a study of indirect comparisons of effectiveness of regimens DCV + ASV, SMV + PegIFN +RBV and PegIFN + RBV, which used two methods CSL [7]:…”
Section: Analysis Of Efficacy: DCV + Asv Smv + Pegifn +Rbv and Pegifmentioning
confidence: 99%